IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DALAM KURIKULUM NASIONAL - Asep Nursobah; Mohammad Erihadiana; Deden Sofwan Ismail; Atang Suharna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the implementation of Islamic Religious Education (IRE) within the national curriculum at SDN Pasirpari, Pacet Subdistrict, Bandung Regency. The curriculum serves as a guideline that organizes the objectives, content, and teaching methods to achieve quality education. IRE plays a vital role in shaping students' character and morals but faces challenges such as teachers' limited understanding of effective teaching methods and resource constraints. This research employs a qualitative approach with a case study design to identify challenges in implementing IRE and propose solutions. Data were collected through in-depth interviews with IRE teachers and classroom observations. The findings reveal that inclusive and interactive teaching approaches can enhance students' understanding of religious teachings. The study recommends reforms in teaching methods and the integration of technology to improve the effectiveness of IRE. By addressing existing challenges, Islamic religious education is expected to optimally contribute to shaping the character of Indonesia's younger generation. This research contributes to the development of better national education policies and offers recommendations for creating a more relevant and contextual IRE curriculum.